FOREIGN OWNERSHIP, PRODUCTIVITY, AND ECONOMIC CRISIS - Suyanto . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
This paper evaluates the productivity benefit from the present of foreign ownership in manufacturing firms. The productivity benefit is analysed for the period before crisis (19881996) and the period crisis onwards (1997-2000). Using the methodology of stochastic production frontier, the results show that foreign ownership generates positive productivity benefit to local manufacturing firms, both during the before crisis period and during the crisis onwards period. An interesting result emerges when comparing the two periods. Although positive spillover benefits exist in both periods, the coefficient of FDI Spillovers is larger during the period of crisis onwards, suggesting that the productivity benefit increase after economic crisis. These findings support an argument by Takii (2007) that economic crisis has positive impact on the productivity spillovers of FDI.